Narrow Pedestrian Corridors and Utilitarian Walker Satisfaction of Gajayana Street, Malang City - Shafwan Naufal Qurniawan; Wisnu Sasongko; Chairul Maulidi (Jurnal Fondasi, 2026)
Pedestrian corridor quality is commonly assessed through walkability, yet objective physical measures do not always reflect how constrained streets are experienced by everyday users. This study examines the relationship between walkability and user satisfaction across four segments of Gajayana Street, Malang, a narrow corridor used predominantly by utilitarian walkers. A quantitative descriptive approach was applied through field observation and a pedestrian perception survey involving 136 respondents. Walkability was measured using weighted infrastructure indicators, while user satisfaction was evaluated using the Customer Satisfaction Index (CSI). The results show that Segments 1, 2, and 3 were classified as not walkable, while Segment 4 performed better and reached the waiting to walkable category. Satisfaction followed a similar overall pattern, but not in strict proportion to physical conditions. Some segments with limited pedestrian support still received relatively better user responses when they remained usable for routine mobility and offered acceptable safety. These findings show that pedestrian corridor quality in narrow urban streets should be interpreted not only through infrastructure provision, but also through how everyday users assess practical usability under constrained conditions.